Optimisation and analysis of battery storage integrated into a wind power plant participating in a wholesale electricity market with energy and ancillary services. (1st November 2022) - Naemi, Mostafa; Davis, Dominic; Brear, Michael J.
Abstract: This paper examines the optimal performance of a wind farm and an integrated battery storage system in a wholesale electricity market. Participation in both the energy and Frequency Control Ancillary Services (FCAS) markets and imperfect generation forecasting are all considered. This problem is formulated as an optimisation that maximises the Net Present Value (NPV) of the wind farm and the battery while considering different market conditions and technical constraints. It is found that several, more advanced approaches to the integration and control of wind farm-battery systems can yield significant financial benefits to the asset owner by providing useful system services. These are not solely energy and FCAS services since all the considered approaches can also improve the wind farm's ability to regulate its own power generation. As such, a battery that is integrated with a wind farm can create greater value than a stand-alone battery of the same size offering the same energy and FCAS services. Furthermore, realisation of these opportunities appears to be consistent with a relatively conventional wholesale market framework. Highlights: Optimisation of wind farm and integrated battery storage providing energy and FCAS. Ancillary services provision can generate significant financial benefit. A battery integrated with a wind farm is more valuable than a stand-alone battery. Improving forecasting accuracy yields extra revenues and smaller battery size.